The Reality and Trends of Knowledge Sharing among the Students of Mardin University of Turkey - AL Mohammed, Daoud Suleiman; Darra, Omar Mohamed (Journal of Economic, Administrative and Legal Sciences, 2019)
The research aimed to identify the reality and attitude of Mardin university students about knowledge sharing, in addition to identifying channels which students preferred it to sharing knowledge, the motivations that guide students to share knowledge, and the main obstacles that impede the process of sharing knowledge. The research focused on colleges that adopt Arabic as a basic teaching language, the analytical descriptive approach was adopted in this research, a questionnaire was designed based on previous studies to measure the attitudes of students about the process of sharing knowledge, And distributed to (235) students. The results showed that the most important sources of students to obtain their information are course teachers with an average of 3.95. But overall the search process was low, and the aim of most students from knowledge sharing was to clarify and discuss the exam issues by (3.78). The references which course teachers are provided them were the most widely used tools by (3.72), It turns out that students tend to share their knowledge face-to-face by (4.14), but about the attitudes of university students, most of them were aware the value of knowledge and their sharing it, and they considered that helps to improve the process of education by (4.16), and most of them encourage knowledge sharing and consider it good by(4.36). The study also presented a set of recommendations that would contribute to improving the process of sharing knowledge among students in the university institution.
Keywords: knowledge sharing; students; Mardin University; Turkey